Culturally Conceptualizing Trauma: The Windigo in Joseph Boyden’s Three Day Road - Visvis, Vikki (Studies in Canadian Literature, 2010)
<!–[if gte mso 9]> Normal 0 false false false EN-CA X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Despite trauma theorist Cathy Caruth’s optimistic vision of psychopathologies as vehicles for cross-cultural dialogue, current theories privilege Eurocentric discourses and thus are inherently founded on a principle of elision. Joseph Boyden’s novel Three Day Road (2005) responds to this Eurocentric approach to trauma in a literary context. The novel reformulates trauma by depending on the twin discourses of the cannibalizing Windigo figure: namely, its status as a distinctly Native ‘sign’ and its place in racially charged Western appropriations as an indication of Native savagery. Boyden’s Windigo consumes the minds of the two protagonists, Cree snipers Elijah Whiskeyjack and Xavier Bird. Boyden also extends the metaphor of the devouring Windigo to engage in an epic sweep of the historical catastrophes that influenced Canadian Indigenous populations, such as the fur trade, the residential school system, and the First World War.